(untitled) (Raparin Journal of Humanities (RJH), 2024)
When the Iraqi army invaded Kuwait, it quickly followed by a strong international reaction, each one of the United States and its allies in the West and the Gulf countries expressed their opposition and disapproval to this act of Iraq. Not only the aforementioned countries but also some of those countries that considered themselves friends of Iraq like the former Soviet Union condemned this aggressive act of Iraq. Hence, to prevent Iraq from taking further actions to attack some other Gulf countries, the United States began to send troops to Saudi Arabia. Along with the military preparations, Iraq was repeatedly warned to withdraw its forces from Kuwait, but it ignored these demands and did not withdraw from it. Consequently, an international military operation involving 34 countries could expel Iraqi forces from Kuwait from December 17 th to February 24 th 1991. Again, the Kuwaiti ruling family could return to power. In this study, we want to elucidate that although the air force strikes played a role in defeating the Iraqi army, but it was not the main factor in defeating it. In addition, it is true that during the six weeks of the International Allies’ air strikes, they dropped dozens of tons of bombs and missiles on the Iraqi army, and the Iraqi army was not capable of fighting the Allies ground forces. We have also briefly discussed the Gulf War and the reasons that led the Iraqi army to invade Kuwait, then we have discussed the role of the Allied countries’ air forces in this war, whether the air force played a major role in the Gulf War or not. Finally, the effects of the Gulf War on the Iraqi government have been explicated.